2014
DOI: 10.3892/mmr.2014.2821
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside-Rg5 induces apoptosis and DNA damage in human cervical cancer cells

Abstract: Panax ginseng is traditionally used as a remedy for cancer, inflammation, stress and aging, and ginsenoside-Rg5 is a major bioactive constituent of steamed ginseng. The present study aimed to evaluate whether ginsenoside-Rg5 had any marked cytotoxic, apoptotic or DNA-damaging effects in human cervical cancer cells. Five human cervical cancer cell lines (HeLa, MS751, C33A, Me180 and HT-3) were used to investigate the cytotoxicity of ginsenoside-Rg5 using a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…In the present work, the result that ginsenoside Rg5 with low dosage of 10 mg/kg daily can exhibit so good protective effect on cisplatin-induced nephrotoxicity may be due to its good absorption. Recently, Liang et al, have reported that ginsenoside Rg5 had marked genotoxic effects on five human cervical cancer cell lines [ 51 ], however, it exerted contrast cisplatin’s genotoxicity on kidney. This may be because ginsenosides show bidirectional regulation effect on body.…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, the result that ginsenoside Rg5 with low dosage of 10 mg/kg daily can exhibit so good protective effect on cisplatin-induced nephrotoxicity may be due to its good absorption. Recently, Liang et al, have reported that ginsenoside Rg5 had marked genotoxic effects on five human cervical cancer cell lines [ 51 ], however, it exerted contrast cisplatin’s genotoxicity on kidney. This may be because ginsenosides show bidirectional regulation effect on body.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we first converted the major ginsenoside Rb1 to Rg3 by enzymatic bioconversion and, then, transformed ginsenoside Rg3 to Rg5 with acid-assisted high-temperature and high-pressure processing, as Rg5 is a rare ginsenoside that is more active in ginseng. Furthermore, previous studies have highlighted that Rg5 performs an effective and desirable approach for the treatment of cancers [17]. In this study, Rg5 exhibited an evident antitumor effect through apoptosis and autophagy mediated by the PI3K/Akt signaling pathway in human breast cancer.…”
Section: Discussionmentioning
confidence: 67%
“…The roles of DNA damage, autophagy, and apoptosis have highly researched and reviewed for cancer prevention in ginseng research [15] , [16] , [17] , [18] , [19] . PARP inhibitors are currently undergoing clinical evaluation in advanced sporadic prostate cancer both as a single agent and in combination with multiple chemopreventive agents.…”
Section: Resultsmentioning
confidence: 99%